2022
DOI: 10.1021/acs.chemmater.2c01612
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Control of Solution-Processed Cu2SnS3 Films with Thiol–Amine Ink Formulation

Abstract: There is increasing demand for tailored molecular inks that produce phase-pure solution-processed semiconductor films. Within the Cu–Sn–S phase space, Cu2SnS3 belongs to the I2–IV–VI3 class of semiconductors that crystallizes in several different polymorphs. We report the ability of thiol–amine solvent mixtures to dissolve inexpensive bulk Cu2S and SnO precursors to generate free-flowing molecular inks. Upon mild annealing, polymorphic control over phase-pure tetragonal (I4̅2m) and orthorhombic (Cmc21) Cu2SnS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…The external cation doping at the Sn site transforms the monoclinic polymorph into cubic ( F 4̅3 m ). It is worth mentioning that partially (SG: I 4̅2 m ) or fully (SG: F 4̅3 m ) disordered CTS polymorphs can also be obtained by synthesis methods, e.g., colloidal method and high-energy reactive ball milling. , Recently, Koskela et al reported an orthorhombic ( Cmc 2 1 ) CTS polymorph. Polymorphism in these materials offers multiple possibilities of structural manipulation and band engineering to boost the TE performance.…”
Section: Introductionmentioning
confidence: 99%
“…The external cation doping at the Sn site transforms the monoclinic polymorph into cubic ( F 4̅3 m ). It is worth mentioning that partially (SG: I 4̅2 m ) or fully (SG: F 4̅3 m ) disordered CTS polymorphs can also be obtained by synthesis methods, e.g., colloidal method and high-energy reactive ball milling. , Recently, Koskela et al reported an orthorhombic ( Cmc 2 1 ) CTS polymorph. Polymorphism in these materials offers multiple possibilities of structural manipulation and band engineering to boost the TE performance.…”
Section: Introductionmentioning
confidence: 99%